Identifying Drug Prescription in Newly Diagnosed Hypertension Patients in India - Thomas Alexander; Jagdish S. Hiremath; Jitendra P. S. Swahney; Subhash Chandra; Peeyush Jain; Praveen Chandra; Nakul Sinha; T. Sashikanth; Yugandhar Bachhu; Anil Balachandran; Pathiyil Balagopalan Jayagopal; T. Govindan Unni; et al. (The Journal of Clinical Hypertension)
ABSTRACT This study evaluated initial antihypertensive drug prescription patterns in Indian healthcare settings. An observational, cross‐sectional, prospective prescription registry analyzed prescriptions for 4723 newly diagnosed hypertension patients. Additionally, it investigated the extent to which physicians adhered to either European or Indian hypertension guidelines. Angiotensin receptor blockers (ARBs) were the most commonly prescribed drugs, given to 79% of patients, followed by calcium channel blockers (CCBs) at 55%. Diuretics and beta‐blockers (BBs) were prescribed to 27% and 17% of patients, respectively. Monotherapy was administered to 35% of patients, while combination therapies were more prevalent, with dual therapy at 51% and regimens involving three or more drugs prescribed to 14%. Among multi‐drug treatments (n = 3082, 65%), 98% received fixed‐dose combination tablets. The most common combinations were ARB + CCB (26%), ARB + diuretic (12%), and ARB + CCB + diuretic (8%). Key predictors for an increasing number of prescribed drugs included statin use/dyslipidemia, age, blood pressure level, and diabetes. Non‐adherence to hypertension guidelines was evident as 1364 patients classified from moderate to very high risk received monotherapy. Of these, 496 patients had grade 2 or 3 hypertension. Additionally, 88 patients received the undesirable combination of ACEi + ARB, and 267 (15.9%) type 2 diabetes mellitus (T2DM) patients did not receive RAS‐blockers (146 on monotherapy). The findings reveal a trend toward utilizing ARBs, CCBs, and combination tablets, indicating improved adherence to guidelines. However, a significant number of patients did not receive appropriate treatment, highlighting areas for improvement in prescription practices.